Stochastic Stability of Short-Run Market Equilibrium: Comment - Weintraub, E. Roy (Quarterly Journal of Economics, 1970)
I. Introduction, 161. — II. The discrete time model, 162. — III. Definitions, 162. — IV. Some theorems on the linear stochastic model, 163. — V. Application to Walrasian and Marshallian stability, 164. —VI. Conclusion, 166.